The Influence of ESG Disclosures on Financial Distress Considering The Director's Financial Expertise as a Moderating Factor - Sekar Natasya Prameswari; Novita Novita; Imam Nurcahyo Fambudi (Program Studi Akuntansi FPEB UPI, 2024)
This research aims to examine the relationship between Environmental, Social andGovernance disclosures on Financial Distress and Director's Financial Skills as a moderation. This research method is quantitative. The sample for this research is Consumer Cyclical subsector companies listed on the Indonesia Stock Exchange (BEI) for the 2019 - 2021 period. The research data source uses secondary data from financial reports and company annual reports. The sampling technique was carried out using purposive sampling and a sample of 108 samples was obtained. This research uses a panel regression analysis test with a Random Effect Model. The results show that ESG disclosure has a significant influence on Financial Distress by showing a probability value lower than alpha 5%. The Director's Financial Skills variable is also proven to strengthen the relationship between ESG disclosure and Financial Distress with a profitability value of 0.000 or 5% This research aims to examine the relationship between Environmental, Social and Governance disclosures on Financial Distress and Director's Financial Skills as a moderation. This research method is quantitative. The sample for this research is Consumer Cyclical subsector companies listed on the Indonesia Stock Exchange (BEI) for the 2019 - 2021 period. The research data source uses secondary data from financial reports and company annual reports. The sampling technique was carried out using purposive sampling and a sample of 108 samples was obtained. This research uses a panel regression analysis test with a Random Effect Model. The results show that ESG disclosure has a significant influence on Financial Distress by showing a probability value lower than alpha 5%. The Director's Financial Skills variable is also proven to strengthen the relationship between ESG disclosure and Financial Distress with a profitability value of 0.000 or 5%.